Periodic solutions of differential inclusions with retards - Gabor, Grzegorz; Pietkun, Radosław (Topological Methods in Nonlinear Analysis, 2000)
The paper is devoted to study the existence of periodic solutions for retarded differential inclusions. The nonsmooth guiding potential method is used and topological degree theory for multivalued maps is applied.